Preservation of Lymphocyte Immunophenotype and Proliferative Responses in Cryopreserved Peripheral Blood Mononuclear Cells from Human Immunodeficiency Virus Type 1-Infected Donors: Implications for Multicenter Clinical Trials - Reimann, Keith A. (American Society for Microbiology (ASM), 2000)
Human immunodeficiency virus type 1 (HIV-1) infection results in impaired immune function that can be measured by changes in immunophenotypically defined lymphocyte subsets and other in vitro functional assays. These in vitro assays may also serve as early indicators of efficacy when new therapeutic strategies for HIV-1 infection are being evaluated. However, the use of in vitro assays of immune function in multicenter clinical trials has been hindered by their need to be performed on fresh specimens. We assessed the feasibility of using cryopreserved peripheral blood mononuclear cells (PBMC) for lymphocyte immunophenotyping and for lymphocyte proliferation at nine laboratories. In HIV-1-infected patients with moderate CD4(+) lymphocyte loss, the procedures of density gradient isolation, cryopreservation, and thawing of PBMC resulted in significant loss of CD19(+) B cells but no measurable loss of total T cells or CD4(+) or CD8(+) T cells. No significant changes were seen in CD28(−) CD95(+) lymphocytes after cell isolation and cryopreservation. However, small decreases in HLA-DR(+) CD38(+) lymphocytes and of CD45RA(+) CD62L(+) were observed within both the CD4(+) and CD8(+) subsets. Fewer than 10% of those specimens that showed positive PBMC proliferative responses to mitogens or microbial antigens lost their responsiveness after cryopreservation. These results support the feasibility of cryopreserving PBMC for immunophenotyping and functional testing in multicenter AIDS clinical trials. However, small changes in selected lymphocyte subsets that may occur after PBMC isolation and cryopreservation will need to be assessed and considered in the design of each clinical trial.